Narrativas sobre la experiencia de violencia en las relaciones del noviazgo en un grupo de jóvenes perteneciente a la universidad Antonio Nariño - Arias Mindiola, Andrea Carolina; Herrera, Michael Steves (Universidad Antonio Nariño, 2021)
The present study aims to describe the meanings attributed to narratives about experiences of violence in dating relationships, in a group of young people belonging to the University Antonio Nariño. It was counted on the participation of 4 young people, who went through different violent scenarios in their dating relationships. Those significant to the aforementioned aspect, were obtained through unstructured interviews and analyzed by the following five categories: meanings attributed to communication distortions that lead to situations of jealousy in the couple relationship, meanings attributed to physical, verbal and emotional, meanings attributed to symmetry in the couple's relationship, meanings attributed to the lack of support and beliefs of the family of origin, and meanings attributed to the establishment of limits and life project in the couple relationship. On the other hand, the main findings are manifested within the violence in dating relationships, which refer to violent episodes, that tend to show up constantly, in physical violence, verbal and psychological, which are considered more prevalent in the participants, within the investigation.